2001
DOI: 10.1128/jvi.75.15.6884-6893.2001
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Serotype 4 (AAV4) and AAV5 Both Require Sialic Acid Binding for Hemagglutination and Efficient Transduction but Differ in Sialic Acid Linkage Specificity

Abstract: Adeno-associated virus serotype 4 (AAV4) and AAV5 have different tropisms compared to AAV2 and to each other. We recently reported that ␣2-3 sialic acid is required for AAV5 binding and transduction. In this study, we characterized AAV4 binding and transduction and found it also binds sialic acid, but the specificity is significantly different from AAV5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
292
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(312 citation statements)
references
References 40 publications
18
292
0
2
Order By: Relevance
“…AAV5 primarily uses N-linked sialic acid for binding, whereas AAV4 preferentially uses O-linked sialic acid for attachment. 45,46 The attachment receptors for AAV1 and AAV6…”
Section: Aav Attachment Receptors and Coreceptorsmentioning
confidence: 99%
“…AAV5 primarily uses N-linked sialic acid for binding, whereas AAV4 preferentially uses O-linked sialic acid for attachment. 45,46 The attachment receptors for AAV1 and AAV6…”
Section: Aav Attachment Receptors and Coreceptorsmentioning
confidence: 99%
“…59 New purification methods were therefore required for new AAV vector types. The observation that 2,3-linked sialic acid is required for AAV4 and AAV5 cell entry 60,61 led to the development of a single-step affinity chromatography for purification of AAV5. 62 The affinity matrix for capture of AAV5 particles consisted of a sialic acid-rich protein called mucin that was covalently coupled to CNBractivated Sepharose (Amersham Biosciences).…”
Section: Purification By Affinity Chromatographymentioning
confidence: 99%
“…4,5 The differences in binding affinity to different receptors among the various serotypes are likely to be accounted for by differences within these structural determinants, since the key heparin-binding residues are different on nonheparin-binding serotypes. 6,7 Receptor-targeted capsid mutants and alternative serotypes broaden the host range for rAAV-mediated gene transfer…”
Section: Structural Biology Of Aav Opens the Door To New Vector Designsmentioning
confidence: 99%
“…Comparison with vectors packaged in AAV5-based capsids, which utilize N-linked sialic acid as an attachment receptor indicated that this receptor abundance issue could be a major limiting factor to the efficiency of airway epithelial cell transduction. 6,7 The potential utility of the newly available pseudotyped rAAV vectors for improved transduction of other organs, such as liver and muscle have also been studied. 8,9 These tend to indicate a significant advantage of rAAV1 vectors for muscle transduction and of rAAV6 in the liver.…”
Section: Structural Biology Of Aav Opens the Door To New Vector Designsmentioning
confidence: 99%
See 1 more Smart Citation